2013
DOI: 10.1142/s0219633613400014
|View full text |Cite
|
Sign up to set email alerts
|

Exponential Propagators (Integrators) for the Time-Dependent Schrödinger Equation

Abstract: The time-dependent Schrödinger Equation (TDSE) is a parabolic partial differential equation (PDE) comparable to a diffusion equation but with imaginary time. Due to its first order time derivative, exponential integrators or propagators are natural methods to describe evolution in time of the TDSE, both for time-independent and time-dependent potentials. Two splitting methods based on Fer and/or Magnus expansions allow for developing unitary factorizations of exponentials with different accuracies in the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 82 publications
0
44
0
Order By: Relevance
“…(1), thus providing initial states which are eigenstates of the grid. 45 The molecular ionization potential energies for the three lowest electronic states are, respectively, I p (1sσ g ) = 1.08 a.u., I p (2pσ u ) = 0.65 a.u., and I p (2pπ u ) = 0.43 a.u. It has been shown that MPADs exhibit a rotation angle with respect to the molecular and laser polarization axes, which mainly arises from the effects of the nonspherical asymmetric molecular Coulomb potential and the helicity of the ionizing photons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1), thus providing initial states which are eigenstates of the grid. 45 The molecular ionization potential energies for the three lowest electronic states are, respectively, I p (1sσ g ) = 1.08 a.u., I p (2pσ u ) = 0.65 a.u., and I p (2pπ u ) = 0.43 a.u. It has been shown that MPADs exhibit a rotation angle with respect to the molecular and laser polarization axes, which mainly arises from the effects of the nonspherical asymmetric molecular Coulomb potential and the helicity of the ionizing photons.…”
Section: Resultsmentioning
confidence: 99%
“…(1) is solved numerically by a secondorder split-operator method in the time step δt combined with a fifth order finite difference method and Fourier transform technique in the spatial steps δ ρ, δθ, and δz. 28,44,45 The time step is taken to be δt = 0.01 a.u. = 0.24 as, the spatial discretization is δ ρ = δz = 0.25 a.u.…”
Section: Methodsmentioning
confidence: 99%
“…The TDSE (2a) was solved using a second-order operator splitting scheme in both 1D and 2D cases [70]. Derivatives of the wave function with respect to the electron position (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…We solve the equations of motion Eqs. (7) and (14) using a second-order exponential integrator [44,45]. Equation (7) is integrated as, c (1)…”
Section: Step 3: Computation Of G Lmmentioning
confidence: 99%